LA REGULACIÓN DE LA MINERÍA ARTESANAL VIOLENTA LOS PRINCIPIOS DE SOSTENIBILIDAD Y SUSTENTABILIDAD DE LA CONSTITUCIÓN - Amay Medina, José Luis (2017)
The research is the subject of this work that I put to the consideration of the National University of Loja arises from the need to make a problem analysis entitled: AL allowed to Artisanal ONLY THE USE OF TECHNOLOGY AND HAND TOOLS ARE VIOLENT ENVIRONMENTAL PRINCIPLES SET FORTH IN THE CONSTITUTION. THERE CONTRADICTION BETWEEN THE CONSTITUTION, THE MINING LAW AND THE LAW OF ENVIRONMENTAL MANAGEMENT TO ALLOW CRAFTSMANSHIP VIOLENT PRINCIPLES OF SUSTAINABILITY AND SUSTAINABILITY "arising from a social problem that directly attacks the principles of sustainability and sustainability of the Constitution following the use of manual tools and technologies in artisanal mining activity. While artisanal mining is considered to support that aims to satisfy personal, associative or a certain group of people as entrepreneurship need by current government in order to eradicate unemployment which has granted an exemption to this activity sparing the payment of royalties and patents. What produced the targeting with the universal principles of environment by excessive use of sierto chemicals such as cyanide and mercury, where mercury from a higher degree of contamination affected the flora and fauna, causing damage to the floor , disappearance of certain species of plants and animals, watersheds tend to have their polluted water and thus affects all 6 who use water use for either drinking water to drink, give the plants and the health of mineworkers who endanger their lives and the lives of their families. Despite the existence of control by the state for the use of mercury little or nothing it has served and is still used illegally and especially so crudely, the Regulations of the Special Scheme for Small Mining and Artisanal Mining prohibits the use of mercury within the activity of artisanal mining and its effect requires mine owners opt for new alternatives for the recovery of metals and for the relevant control is supported Environmental Regulation for mining Activities states that the mining company should seek technical alternatives environmental eliminate the use of mercury in accordance with the third transitional provision of the Organic Law Reform to the mining Act that to eradicate the use of mercury in mining activities or corporations, domestic or foreign persons, rights holders miners during the period of two years must apply alternative methods that will eliminate the use of mercury during the recovery process ore, if not meet proper appropriate penalty to revocation of the mining law be applied without prejudice to the sanctions order criminal to take place, in order to guarantee the Constitutional rights to live in a healthy environment and guarantee the right to health for people in this case for artisanal miners; and above all ensure the universal principles of Sustainable Development held in Rio de Janeiro in 1992, on environment and development, for present and future generations. But a procedure for obtaining authorization for the use of mercury for mining activities is presented by the respective authorization which brings not provide a proper 7 alternative to eradicate mercury, why not created or encouraged the respective technological alternatives for artisanal miners are trained to avoid damage to the environment and ensure the health of citizens in general.